Exploring the Synergistic Effects of Tax Policies, HRM Practices, and Strategic Marketing on Organizational Financial Performance: A SEM-PLS Analysis - Putra, Aditya Halim Perdana Kusuma; Mariam, Siti; Rozamuri, Arif Murti; Yusuf, Marwah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this study is to examine the synergistic effects of tax policies, Human Resource Management (HRM) practices, and strategic marketing initiatives on organizational financial performance, with a focus on understanding how these elements interact to enhance market competitiveness and operational efficiency in a rapidly evolving business environment. This study employed a descriptive correlational research design to investigate the synergistic effects of tax policies, HRM practices, and strategic marketing initiatives on organizational financial performance. The study utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the complex relationships among these variables, capturing data from a cross-sectional sample of 245 valid responses from middle to large-scale enterprises. Data were collected via a structured online survey that included both validated scales and newly developed items tailored to the constructs of interest. The analysis proceeded in two stages: first, assessing the measurement model for validity and reliability, and second, evaluating the structural model to test the hypothesized relationships. SEM-PLS was chosen for its ability to handle complex models with latent variables, even with small to medium sample sizes, providing robust insights into the factors that drive organizational financial performance. The results of this study reveal significant relationships between HRM Practices, Strategic Marketing Initiatives, Tax Policies, and Organizational Financial Performance, with Market Competitiveness and Operational Efficiency acting as critical mediators. The indirect effects further supported these findings. HRM Practices, Strategic Marketing Initiatives, and Tax Policies all indirectly contributed to Organizational Financial Performance through Market Competitiveness and Operational Efficiency, with all paths showing statistical significance. These results emphasize that the synergistic alignment of HRM, marketing, and tax strategies is crucial for achieving superior financial outcomes, with Market Competitiveness and Operational Efficiency serving as essential pathways in this process.